New taxonomic status and new replacement name for Macednus Emeljanov, 1962 (Hemiptera: Cicadellidae: Deltocephalinae) - Xing, Ji-Chun; Li, Zi-Zhong (Zootaxa, 2011)
Emeljanov (1962) established the leafhopper genus Macednus with the type species Macednus marginatus Emeljanov, 1962 from USSR (Maritime Territory). Later, Vilbaste (1967) placed Macednus Emeljanov, 1962 as a junior subjective synonym of Albicostella Ishihara, 1953. Albicostella has Thamnotettix albicosta Matsumura,1914 as its type species. Oman, et al. (1990) followed Vilbaste (1967) in treating Macednus as a junior synonym of Albicostella and included the genus in the tribe Athysanini of subfamily Deltocephalinae (Hemiptera: Cicadellidae). Later, Hamilton (1975) reinstated Macednus as a separate genus.